Pediatric-onset Inflammatory Bowel Disease Has Only a Modest Effect on Final Growth: A Report From the epi-IIRN. Issue 2 (August 2021) - Assa, Amit; Assayag, Noa; Balicer, Ran D.; Gabay, Hagit; Greenfeld, Shira; Kariv, Revital; Ledderman, Natan; Matz, Eran; Dotan, Iris; Ledder, Oren; Yerushalmy-Feler, Anat; Turner, Dan; et al.
ABSTRACT: Objectives: The impact of pediatric-onset inflammatory bowel disease (IBD) on growth is debated. We aimed to investigate the effect of IBD on anthropometric measures at young adulthood. Methods: Children diagnosed with Crohn disease (CD) or ulcerative colitis (UC) (2005–2019) were identified in a national database along with matched non-IBD controls. Results: Overall, 2229 IBD cases (68% CD) were matched to 4338 controls. Only females with CD differed in final height from controls ( z scores: −0.37 ± 1.09 vs −0.25 ± 1.06, respectively; P = 0.01), corresponding to a mean difference of 0.7 ± 0.2 cm (all females) and 1.2 ± 0.3 cm in females diagnosed <14 years ( P = 0.02). Final height was reduced in both sexes according to adjusted mean height difference analysis (−0.43 cm, 95% confidence interval −0.85 to −0.02; P = 0.04). This difference increased in patients with CD who underwent abdominal surgery (−0.91 cm, 95% confidence interval −1.39 to −0.42; P = 0.01). The proportion of patients with CD achieving final height z scores of −1 and zero differed significantly from controls for both males (71.1% and 34.8% vs 79.1% and 43.0%, respectively; P < 0.001) and females (67.7% and 30.4% vs 79.6%, and 43.3%, respectively; P < 0.001). Patients treated with anti-tumor necrosis factor agents during growth potential had similar height improvement to other regimens. Predominantly, patients with CD were leaner, with a greater proportion of subjects with underweight, compared with controls. Conclusions: In pediatric-onset IBD, absolute final height was modestly affected by females with CD. Nevertheless, greater proportions of both sexes with early diagnosis of CD failed to achieve normal final height, compared with controls. Abstract : Supplemental Digital Content is available in the text